MEASURING ENGLISH PROFICIENCY OF INDONESIAN BANKS’ FRONT-LINERS - Guritno, Agung (Universitas Nusantara PGRI Kediri, 2020)
The industrial revolution and the free market policy agreement among the countries in the world brings severe impacts in many sectors, especially economics. As one of the supporting economics systems, the banking sector also faces the most significant challenge ever. The banks should provide their best services to the customers; otherwise, they will quickly leave them. This study determines how the front-liners’ (Customer Services and Tellers) can speak English to support their workplace activities. There are ten customer services and eight tellers from four banks as the respondents. The method used is quantitative, with a structured interview as the instrument to collect data. The researcher then measured the result of the talks by using a scoring rubric. The study's development reveals that those front-liners have different English proficiency levels, ranging from high to low. The banks where they work and the universities where they learned are responsible for overcoming this. It could be by restricting the new employee's entrance exam, providing training programs for the employees, and updating the universities' curriculum with the latest material to prepare their students to face the job market, which is very demanding today.